The Importance of Myths and Legends in Shaping Polish Historical Policy in the 21st Century: Contemporary Determinants - Wojtaszak, Andrzej (Historia i Polityka, 2023)
The aim of the article is to analyse the value of myth and legend in shaping historical policy. The activity of politicians and their influence on shaping historical policy is most often associated with political change, secession, reconstruction, or state renewal. The creators of these transformations seek to find historical connections in the past that would legitimise the changes and the purposefulness of the actions taken by the government. Historians play a considerable role in such endeavours; however, they should not forget historical truth, which may conflict with political needs.